Electronic structure studies of germanium, tin and their alloy - Lim, Dali. (2009)
Vienna Ab-initio Simulation Package (VASP) is used to calculate the energy band structure of Germanium, Tin and their alloy. There are a total of 5 different Density Functional Theory methods used in this project: Project Augmented Wave-Local Density Approximation method (PAW-LDA), Project Augmented Wave-Generated Gradient Approximation method (PAW-GGA) , Project Augmented Wave-Perdew Burke Ernzerhf method (PAW-PBE), Ultrasoft pseduopotential-Local Density Approximation method (USP-LDA) and Ultrasoft pseduopotential- Generated Gradient Approximation method (PAW-GGA) to study the electronic structure of Germanium, Tin and their alloy. In addition, the lattice constant, the effective mass and the luttinguer parameters for both Germanium and Tin are calculated using VASP. Origin 7.5 was used for plotting the various band diagrams and for fitting purpose.